The effect of alcohol abuse on high-risk sexual behaviour among students in Mafikeng - Mabille, Philip Adam Neo (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2009.